Pola Interaksi Anak dan Orangtua Selama Kebijakan Pembelajaran di Rumah - Putro, Khamim Zarkasih; Amri, Muhammad Adly; Wulandari, Nuraisah; Kurniawan, Dedek (Prodi PAI STAI Sumatera Medan, 2020)
This study aims to reveal the effectiveness of the implementation of learning from home, and patterns of interaction between parents and children during learning from home. Set the pattern of interaction between parents and children during the learning policy from home is very important to do, so that children can voluntarily learn, and parents can easily control and improve children's learning activities and outcomes at home. The method used in this research is a qualitative study based on descriptive studies, meaning that research methods require results in the form of descriptions, or a complete and complex depiction of research data and facts. In this case the depiction in question is the pattern of interaction between parents and children during distance learning or at home during the Covid-19 pandemic. The results showed that the position of parents in managing interactions with their children is very important for the continuity of learning. Interaction patterns of interaction between parents and children as the findings of this study show two patterns, direct interaction; in this case parents and children together follow the learning provided by the teacher. Indirect interaction in this case parents only as a facilitator, for the implementation of learning.